Level Of Flood Disaster Vulnerability In Hudi Laran District, Dom Aleixo, Dili City, Timor-Leste - Pereira, Alexandre (Journal of Civil Engineering, Planning and Design, 2023)
An area is said to be prone to flooding if the area has a high tendency or potential to experience floods. This can be seen from the topography of the area as well as infrastructure such as the provision of flood inundation disposal sites. Meanwhile, to determine the level of vulnerability to flooding can be determined based on the parameters that affect the occurrence of flooding. This study aims to determine the area's vulnerability to flooding in residential areas along the Aimutin road in Hudi Laran-Timor Leste. This research was conducted quantitatively using a survey method by distributing questionnaires to 37 research samples. The population in this study included the entire residential area along Jalan Aimutin in the Hudi Laran area, Biropite Village, Dom Aleixo District, Dili City, Timor-Leste and the subjects of the study were the community, using stratified random sampling techniques by Purposive and Accidental Sampling. The results of the study based on the calculation of the flood hazard level parameter score show the high category with inundation duration 48 hours, while the frequency of flood inundation in the area shows the medium category with a presentation of 75.8% or as many as 2-5 incidents in one year. Calculation of the area's vulnerability level to flooding shows that out of 37 research samples, 10 samples fall into the low vulnerability category, the remaining 18 research samples show moderate vulnerability and 9 other samples fall into the high vulnerability category.